Conceptual Foundations of Legal Security and its Provision: Evolution of Approaches - BELYAEV, V. P.; CHAPCHIKOV, S. Y.; BELYAEVA, G. S.; BUTOVA, E. V.; KRYLOVA, Y. A. (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505//jarle.v9 3(33).14, 2018)
The article studies the conceptual approaches to definition of legal security and its provision in the international level. Evolution of views on legal security of person, society, and state in the social and legal aspects is viewed, and attention is paid to the necessity for strengthening of the legal component of the process of provision of the national and international security. The main determinants for provision of legal security are set and systematized. The methodology of the work is based on the systemic and integrated approach to the analyzed legal entities, which allow viewing them as systems with internal and external connections; comparative and legal approach, which supposes exchange of information at the level of the global legal science and search for new parameters of comparing the phenomena of legal reality of various countries. As a result of the research, the conceptual legal approaches to understanding of legal security were systematized; these approaches allow determining it in space, as to the national interests of a certain country’s population, as to state’s sovereignty; the legal essence of this notion is determines, as well as the principles of provision of personal, public, and national (state) security at the international level.